Therapeutic Hypothermia for Patients with Out-of-Hospital Cardiac Arrest in North Carolina. (2nd September 2016) - Rao, Meena P.; Dupre, Matthew E.; Pokorney, Sean D.; Hansen, Carolina M.; Tyson, Clark; Monk, Lisa; Pearson, David A.; Nelson, R. Darrell; Myers, Brent; Jollis, James G.; Granger, Christopher B.
Abstract: Introduction : While therapeutic hypothermia has been the standard of care for patients who suffer out-of-hospital cardiac arrest (OHCA), recent trials have led to an advisory statement recommending a focus on targeted in-hospital temperature management and against initiation of prehospital hypothermia with rapid infusion of cooled saline. The aim of this study is to review the experience with therapeutic hypothermia in North Carolina.Methods: We studied patients who suffered OHCA in North Carolina in 2012 captured in the CARES database as part of the Heart Rescue Project. We excluded patients without return of spontaneous circulation and patients without an advanced airway placed in the field to reduce selection bias. Bivariate distributions and multivariate logistic regression models were used to examine differences in survival to discharge and positive neurological outcome.Results: 847 patients were included in the analysis of pre-hospital hypothermia. Of these patients, 55% received prehospital hypothermia. Prehospital initiation of hypothermia was associated with higher survival to hospital discharge (OR 1.55, 95% CI 1.03–2.32) and improved neurologic outcome at discharge (OR 1.56 95% CI 1.01–2.40). In patients who survived to hospital admission ( n = 537), in-hospital hypothermia was associated with a non-significant trend toward better survival to discharge (p = 0.18).Conclusion: We found that patients who received prehospital hypothermia had improved outcomes, a finding that may be due to a greater likelihood of receiving in-hospital hypothermia or a reflection of higher quality of pre-hospital care. These findings support ongoing efforts to improve all aspects of the chain of survival after cardiac arrest.